Food chain and carbon accumulation in mangrove plantation areas in Thailand / Shigeru Kato ... [et al.] - Kato, Shigeru; Boonming, Savettachat; Chantrapromma, Kan; Thongkao, Suthira; Panichart, Sangob; Aksornkoae, Sanit; Tongnunui, Prasert; Tarangkoon, Woraporn; Kojima, Toshinori (Universiti Teknologi MARA, Pulau Pinang, 2015)
Mangrove forests provide numerous ecosystem services, including nutrient cycling, sediment trapping, protection from cyclones and tsunami, habitat for numerous organisms and wood for fuel and lumber. It is being a unique habitat for several fresh and saline tolerant species. The present research aims to study the carbon accumulation and food cycle system in the rehabilitated mangrove site of Nakhon Si Thammarat, southern part of Thailand. The mangrove rehabilitation sites, at the abandoned shrimp ponds and new mud flat areas, have been taking place since 1998 by participatory planting activity. Almost seven million mangrove trees were planted in 1,200 ha. It is observed that the rehabilitated mangrove site can be habitat for increasing the population of the species like crab, shell, shrimp and fish. It is also found that the δ15N content in the living organism is gradually increased from small phytoplankton to large fishes in the food chain system. Conversely, it is observed that there is significant change in the δ13C value during the food chain system. The data analysis reveals that the carnivorous fishes involve in 12th to 13th step of the food chain system which starts from the falls of mangrove leaves of the rehabilitated mangrove forest. Carbon content of soil in the rehabilitated mangrove forest was gradually increased with planting age from the state of the abandoned shrimp ponds and new mud flat areas. The rehabilitated mangrove forest would be as a sink source for atmospheric carbon and rich biodiversity of the estuaries ecosystem.